Effects of orientation and twin boundary spacing on the mechanical behaviour of γ-TiAl alloy. Issue 3 (11th February 2022) - Cao, Hui; Chen, Wenke; Rui, Zhiyuan; Yan, Changfeng
ABSTRACT: γ-TiAl alloy is a promising structural material applied in the aerospace and automotive industries. However, its mechanical behaviour is still not well characterised at the atomic scale. In this work, the roles of orientation and twin boundary (TB) spacing on the mechanical properties and deformation behaviours of γ-TiAl alloy are investigated by molecular dynamics simulation with embedded-atom potential under shear loading. The simulation results reveal that the shear modulus is the largest when shearing along [100] and smallest along [ 01 1 ¯ ] orientation. The yield stress is the highest of [100] and lowest of [ 11 2 ¯ ] orientation. The deformation mechanism and the strain hardening effect differ with orientations. Moreover, it is found that TB migration perpendicular to the loading direction is good at strengthening γ-TiAl alloy. Specifically, 3.79 nm is the critical spacing corresponding to the maximum stress, average peak stress, stress relaxation and the largest strain hardening factor. The shear modulus and yield stress are independent of the TB spacing. The study shows that 3.32 nm is the critical spacing for the TB to annihilate. More importantly, TB migration is the main deformation mechanism at first. Then, it is controlled by the interaction between dislocation-dislocation and dislocation-TB at different TB spacings.